1994
DOI: 10.1093/oxfordjournals.aje.a117278
|View full text |Cite
|
Sign up to set email alerts
|

Premenopausal Estradiol Levels and the Risk of Breast Cancer: A New Method of Controlling for Day of the Menstrual Cycle

Abstract: Levels of total estradiol in premenopausal women vary widely over the course of the menstrual cycle with a spike at the time of ovulation and dissimilar patterns pre- and post-ovulation. Evaluating the association between breast cancer and premenopausal measurements of total estradiol when the measurements cannot be taken on a uniform day of the cycle is therefore a difficult methodological challenge. In a matched case-control study of breast cancer nested within a prospective study, premenopausal serum sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 0 publications
1
46
0
Order By: Relevance
“…In rats and mice, DHEA feeding reduces fat accumulation in both genetic-and diet-induced obesity models and has protective effects against insulin resistance induced by a high-fat diet (33,42). Studies have reported an association between low levels of serum or urine DHEA or DHEA metabolites and increased breast cancer risk in premenopausal women (48)(49)(50)(51)(52)(53). The relationship between endogenous androgens, such as DHEA, and breast cancer risk is less clear with both epidemiological and experimental data providing conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…In rats and mice, DHEA feeding reduces fat accumulation in both genetic-and diet-induced obesity models and has protective effects against insulin resistance induced by a high-fat diet (33,42). Studies have reported an association between low levels of serum or urine DHEA or DHEA metabolites and increased breast cancer risk in premenopausal women (48)(49)(50)(51)(52)(53). The relationship between endogenous androgens, such as DHEA, and breast cancer risk is less clear with both epidemiological and experimental data providing conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the disease on serum hormone concentrations can only be excluded by prospective studies. Only three prospective studies have reported oestradiol concentrations in premenopausal women and none found a statistically significant association between serum oestradiol concentration and risk of developing breast cancer (Wysowski et al, 1987;Helzlsouer et al, 1994;Rosenberg et al, 1994).…”
mentioning
confidence: 99%
“…The opposite was previously found by Wysowski et al [29], in the same cohort study. Rosenberg et al [30] reported, in a case-control study nested in the New York University Women's Health Study, similar estradiol levels in cases and controls (although further adjustments for stage of menstrual cycle at blood drawing suggested that estradiol was on average non-significantly higher in cases). Kabuto et al [22] found in the prospective cohort study conducted in Japan higher levels ofbioavailable estradiol in breast cancer cases than in controls.…”
Section: Sex Hormones and Breast Cancer In Premenopausal Womenmentioning
confidence: 98%
“…Results from the prospective study conducted in the island of Guernsey (UK) by Key and colleagues showed that premenopausal breast cancer cases excreted less estrogen than controls when estrogens were determined in urine [31] and that estrogen levels were higher in cases than in controls when the hormones were determined in blood, although the difference was small and not statistically significant [32]. The number of breast cancer cases in those studies ranged between 22 [25] and 79 [30]. Several of those studies tried to control the ovarian phase variability using time interval between the date at specimen collection and the date at the subsequent menstrual period either as a matching variable or variable to adjust for in the analysis [30][31][32].…”
Section: Sex Hormones and Breast Cancer In Premenopausal Womenmentioning
confidence: 99%
See 1 more Smart Citation